Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1073/pnas.1311725110
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei suppresses Caenorhabditis elegans immunity by specific degradation of a GATA transcription factor

Abstract: Burkholderia pseudomallei is a Gram-negative soil bacterium that infects both humans and animals. Although cell culture studies have revealed significant insights into factors contributing to virulence and host defense, the interactions between this pathogen and its intact host remain to be elucidated. To gain insights into the host defense responses to B. pseudomallei infection within an intact host, we analyzed the genome-wide transcriptome of infected Caenorhabditis elegans and identified ∼6% of the nematod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…Such expression analyses have been performed with mutants of the p38 MAPK, JNK MAPK, TGF-␤ and the ILR cascades (for example pmk-1(km25) for p38 MAPK (Bond et al, 2014), jun-1(gk557) for JNK (Uno et al, 2013), dbl-1(ctIs40) overexpression for TGF-␤ (Roberts et al, 2010) and daf-16(mu86) for ILR (Murphy et al, 2003)). Similar expression analysis was performed for mutants of GATA transcription factors, including a mutant for the GATA transcription factor gene elt-2, which is known to contribute to immunity against some gut-infecting pathogens such as Pseudomonas aeruginosa, Salmonella typhimurium, Enterococcus faecalis, Cryptococcus neoformans or Burkholderia pseudomallei (Kerry et al, 2006;Shapira et al, 2006;Lee et al, 2013). ELT-2 is the major transcriptional regulator in the C. elegans intestine, controlling the constitutive expression of most of the genes necessary for maintenance of intestinal function (McGhee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such expression analyses have been performed with mutants of the p38 MAPK, JNK MAPK, TGF-␤ and the ILR cascades (for example pmk-1(km25) for p38 MAPK (Bond et al, 2014), jun-1(gk557) for JNK (Uno et al, 2013), dbl-1(ctIs40) overexpression for TGF-␤ (Roberts et al, 2010) and daf-16(mu86) for ILR (Murphy et al, 2003)). Similar expression analysis was performed for mutants of GATA transcription factors, including a mutant for the GATA transcription factor gene elt-2, which is known to contribute to immunity against some gut-infecting pathogens such as Pseudomonas aeruginosa, Salmonella typhimurium, Enterococcus faecalis, Cryptococcus neoformans or Burkholderia pseudomallei (Kerry et al, 2006;Shapira et al, 2006;Lee et al, 2013). ELT-2 is the major transcriptional regulator in the C. elegans intestine, controlling the constitutive expression of most of the genes necessary for maintenance of intestinal function (McGhee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al 4. had previously demonstrated that ugt–29 was the most robustly induced C. elegans phase II detoxification gene following B. pseudomallei infection of worms.…”
Section: Discussionmentioning
confidence: 99%
“…The inability of antibody to provide high-level protection against B. pseudomallei may also reflect the intracellular lifestyle of the organism. In contrast, there is evidence from studies in Caenorhabditis elegans that the bacterium might recruit the ubiquitin-proteasome system to degrade a GATA transcription factor required for host immune defence [85]. Manipulation of the major histocompatibility complex (MHC) class I processing pathway is a common mechanism by which viral pathogens avoid the induction of protective CD8 + T cell responses [82,83].…”
Section: Why Protective Immunity Is Difficult To Evokementioning
confidence: 99%